Transforming nutritional behaviors of basic school children through school-based participatory nutrition education program: A study protocol - Upreti, Yadu Ram; Devkota, Bhimsen (Interdisciplinary Research in Education, 2022)
Dietary habits build on in the formative years persist across the lifespan; therefore, developing healthy nutritional behaviors is crucial among school-going children. The school education can be a powerful influence in modifying the nutritional behaviors of children. Available evidence indicates that school-based nutrition education may promote improved dietary behaviours of school children if it is integrated with motivation, action, and a supportive environment. This study aims to design, implement and evaluate a school-based participatory nutrition education program (SBPNEP) to transform the nutritional behavior of students through participatory action research (PAR). This study uses a transformative mixed-method design as part of the PAR methodology. Five co-educational community schools are selected from Chitwan district of Nepal following the inclusion criteria of NORHED Rupantran Project under Tribhuvan University. Among the five schools, one is selected as the ‘action school’ where intervention sessions will be implemented. The remaining four schools serve as the ‘reference schools’ where effective intervention components of the action school will be replicated. Basic school students, their parents, basic school science and health education teachers, and school leaders are the co-researchers of this study. Both quantitative tools and qualitative methods will be used to generate the data. Quantitative data will be analyzed using inferential statistics (bivariate and multivariate), whilst the interpretive phenomenological analysis (IPA) method will be used for meaning making process of the qualitative data. Three components of the intervention also said to be PAR cycles: sensitization and motivation’, ‘nutrition pedagogy’ and ‘creating a supportive environment for sustainability’ will be implemented following an iterative process of planning, acting, observing, and reflecting of the PAR cycle. The effectiveness of the intervention activities will be evaluated under three phases: short-term, mid-term, and long-term.